2020
DOI: 10.3168/jds.2019-17557
|View full text |Cite
|
Sign up to set email alerts
|

Moisture content of high-straw dry cow diets affects intake, health, and performance of transition dairy cows

Abstract: The objective of this study was to determine the effect of adding water to a high-straw dry cow diet on feeding behavior, health, and performance of dairy cows. Holstein cows (n = 40) entering their second or greater lactation were enrolled at dry off (~45 d before expected calving) and assigned to 1 of 2 dietary treatments, consisting of a high-straw dry cow total mixed ration [TMR; 36% wheat straw, 41% corn silage, 23% pellet, on a dry matter (DM) basis, formulated for 11.6% crude protein, 1.35 Mcal/kg net e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…Cows will sort a diet where particle size is more easily distinguished (Oelker et al, 2009); as such, it may be possible that lactating cows in the Litherland et al (2013) study sorted more against the long particles because that diet contained a greater proportion of long particles on the top 2 screens as a result of liquid feed inclusion, making the long dietary particles in their diet more distinguishable. Interestingly, Havekes et al (2020b) reported a similar reduction, compared with the current study, in degree of sorting against the longest ration particles when water was added to a high-straw dry cow diet compared with when cows were fed a diet with no added water. It is noteworthy that the liquid feed addition in the current study did not drastically influence the overall DM content of the ration compared with that of the CON diet; accordingly, the observed results in this research are more likely related to non-moisture factors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Cows will sort a diet where particle size is more easily distinguished (Oelker et al, 2009); as such, it may be possible that lactating cows in the Litherland et al (2013) study sorted more against the long particles because that diet contained a greater proportion of long particles on the top 2 screens as a result of liquid feed inclusion, making the long dietary particles in their diet more distinguishable. Interestingly, Havekes et al (2020b) reported a similar reduction, compared with the current study, in degree of sorting against the longest ration particles when water was added to a high-straw dry cow diet compared with when cows were fed a diet with no added water. It is noteworthy that the liquid feed addition in the current study did not drastically influence the overall DM content of the ration compared with that of the CON diet; accordingly, the observed results in this research are more likely related to non-moisture factors.…”
Section: Discussionsupporting
confidence: 81%
“…Forty Holstein cows (parity = 1.9 ± 1.04; mean ± SD) were used in this study, which took place at the University of Guelph Elora Research Station-Dairy Facility (Elora, ON, Canada). This study was performed in conjunction with the study described by Havekes et al (2020b), with both studies sharing the same group of control cows (n = 20). Cows were dried off and enrolled in the study at approximately 45 d before expected calving (actual = 43.2 ± 5.87 d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the sorting behavior may persist in the fresh period with eventual negative consequences. Havekes et al [32][33][34] very recently proposed a variety of strategies to reduce the sorting behavior in low energy diets in the dry period. In a first experiment [32], they demonstrated that prepartum cows being fed a short chop length (2.54 cm screen) of wheat straw is preferable since it was associated with lower serum BHB concentration in the third week postpartum compared to that in cows fed a long chop length (10.16 cm screen) of wheat straw.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%
“…Although a shorter chop length of straw reduced sorting, it did not (completely) eliminate this behavior. In a next set of experiments, Havekes et al [33,34] moisturized the content of high-straw dry cow diets with water or liquid molasses. The hypothesis was that the addition of water to dry-cow diets that are low in moisture would improve DMI and reduce feed sorting, while the addition of liquid molasses will additionally support ruminal cellulolytic microbial growth.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%